2013
DOI: 10.1118/1.4828836
|View full text |Cite
|
Sign up to set email alerts
|

Novel multimodality segmentation using level sets and Jensen‐Rényi divergence

Abstract: Purpose: Positron emission tomography (PET) is playing an increasing role in radiotherapy treatment planning. However, despite progress, robust algorithms for PET and multimodal image segmentation are still lacking, especially if the algorithm were extended to image-guided and adaptive radiotherapy (IGART). This work presents a novel multimodality segmentation algorithm using the Jensen-Rényi divergence (JRD) to evolve the geometric level set contour. The algorithm offers improved noise tolerance which is part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…The segmentation tools evaluated against the pathology in the original publications were mostly simple threshold or adaptive threshold methods. More advanced segmentation methods, which promise to be able to handle realistic tumors with irregular shape and non-uniform activity, have been evaluated in later publications against some of the PSPVs reviewed here [47][48][49][50][51][53][54][55]. Important conclusions have been reached for these more advanced methods, as pointed out in the previous section.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The segmentation tools evaluated against the pathology in the original publications were mostly simple threshold or adaptive threshold methods. More advanced segmentation methods, which promise to be able to handle realistic tumors with irregular shape and non-uniform activity, have been evaluated in later publications against some of the PSPVs reviewed here [47][48][49][50][51][53][54][55]. Important conclusions have been reached for these more advanced methods, as pointed out in the previous section.…”
Section: Discussionmentioning
confidence: 92%
“…They found that the wavelet transform-enhanced FCM resulted in a smaller mean error of the maximal diameter estimation also for the NSCLC lesions. Markel et al [51] also used the MAASTRO NSCLC data set [12] to evaluate their multimodality segmentation tool using level sets and JRD and found that JRD outperformed an SBR method when using only PET and noted further performance improvement when information from both PET and CT is used. Sharif et al [55] used the MAASTRO data set [12] to evaluate an artificial neural network approach.…”
Section: Evaluation Of Pet Segmentation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these methods are based on the assumption that the lesions should be homogeneous [20], and may not obtain a satisfied results on heterogeneous tumors usually. Therefore many researches are focused on improving the traditional region-based method to adapt to the heterogeneous tumors in recent years, and some of them obtained stratified results [21] The fourth kind of methods, represented by level set and active contours [22][23][24][25], are based on the boundary of the object. Though how to locate the boundaries in the noisy and low-resolution PET images is challenging, these methods could overcome the restricted condition of homogeneity and obtain more accurate results.…”
mentioning
confidence: 99%